EXPLORING PROBLEM-BASED LEARNING IMPLEMENTATION IN TEACHING SPEAKING TO SECONDARY SCHOOL STUDENTS - Amalya, Lala Vyona; Sidik Indra Nugraha; Hilmansyah Saefullah (Universitas PGRI Palembang, 2025)
This study investigates the application of Problem-Based Learning (PBL) in developing speaking skills among secondary school students, focusing on both instructional implementation and the obstacles encountered. Conducted at a public junior high school in Karawang, Indonesia, the research adopts a qualitative case study approach, utilizing classroom observations and teacher interviews as primary data sources. The study analyzes the integration of five core PBL stages: problem identification, analytical discussion, independent inquiry, synthesis of findings, and reflective evaluation. Results indicate that the teacher successfully implemented each phase, fostering greater student participation and enhanced speaking confidence. Nonetheless, several impediments such as students’ low motivation, limited command of English, and insufficient learning resources posed challenges to optimal learning outcomes. The study concludes that while PBL offers considerable potential to improve oral communication skills, its success is contingent upon thorough instructional planning and robust institutional support.